Efektivitas Lembaga Sertifikasi Profesi dalam Meningkatkan Peluang Kerja di Balai Besar Pelatihan Vokasi dan Produktivitas Kota Bandung - Zalfa, Lis Haliza; Adji, Widwi Handari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Bandung Vocational and Productivity Training Center (BBPVP) is a Government Training Institution Central Technical Implementation Unit (UPTP) under the Directorate General of Training and Productivity Development, Ministry of Manpower of the Republic of Indonesia, in accordance with Ministerial Regulation No. 21 of 2015 issued by the Ministry of Manpower of the Republic of Indonesia. BBPVP Bandung is responsible for implementing initiatives related to the development, empowerment, and certification of training personnel, instructors, and workers. On February 23, 1952, the Government of the Republic of Indonesia and the Colombo Plan Program launched BBPVP. An area of approximately 3 hectares became the location of BBPVP Bandung on Jalan Jenderal Gatot Subroto No. 170. BBPVP was established as an effort to spread vocational training facilities so that those whose homes were in remote areas could still access them. Examining the relationship between the BBPVP competency test and the caliber of applicants is the main objective of this study. The research approach was quantitative and descriptive. Questionnaires and written records were used to compile the data. Based on the findings, BBPVP is an effective tool to improve the overall standard of the workforce. This was determined from the data collected through questionnaires administered to 64 respondents. Keywords: Effectiveness of Professional Certification Bodies. Job Opportunities